Managing digital innovation in publishing : collaborations and para-organisations for creative change - Hall, Frania (New York, NY : Routledge, 2024)
"Businesses can and do successfully experiment and innovate in digital publishing through collaboration. Many sectors of publishing are still structured around print production, with digital innovation in the consumer arena generally focused on different book formats, such e-books and audiobooks, rather than brand-new types of products. Publishers need to innovate around different sorts of content and digital formats as consumers change their media habits. However, their pricing, business and risk models, and workflows are reflective of a legacy of print publishing; and as print commands so much revenue publishers do not want to derail their main business as they experiment. Drawing on an analysis of collaboration and network theory and four in-depth qualitative case studies in different sectors, this research suggests that collaboration, particularly engaging with the wider creative sector, is key to the sustainable development of new types of products. It points to the characteristics of a successful digital collaboration and explains how to manage publishing innovation alongside the existing business, through para-organisations. Considering novel approaches to innovation, such as iterative software-style approaches and agile project management, as well as new business models, such as those employed in games development, the author shows how introducing new people - from software developers to competitors - can help instill a collaborative mindset within the organization and facilitate constructive experimentation. Managing Digital Innovation in Publishing will be of interest to upper-level students and researchers of (Digital) Publishing and related Media Industries"--
Keywords: Organizational change; Publishers and publishing -- Technological innovations; Information technology -- Management; Electronic publishing; Creative thinking -- Economic aspects -- Research; Business networks -- Computer network resources; LANGUAGE ARTS & DISCIPLINES / Publishing